2006
DOI: 10.1097/01.brs.0000228728.11076.82
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of Superficial Trunk Muscle Activation During Sitting in Nonspecific Chronic Low Back Pain Patients

Abstract: Subclassifying nonspecific chronic LBP patients revealed clear differences in sEMG activity during sitting between pain-free subjects and subgroups of nonspecific chronic LBP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
165
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(180 citation statements)
references
References 34 publications
13
165
1
1
Order By: Relevance
“…It is possible that individuals with greater functional limitations would show changes in muscular activation parameters which would agree with the reports of previous studies [19][20][21][22] . However, the selection of participants with these characteristics was a deliberate decision, since the aim of the present study was to understand the relationships between changes in the activation patterns and mechanical LBP, and not the effects of high levels of pain and disabilities of muscular activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is possible that individuals with greater functional limitations would show changes in muscular activation parameters which would agree with the reports of previous studies [19][20][21][22] . However, the selection of participants with these characteristics was a deliberate decision, since the aim of the present study was to understand the relationships between changes in the activation patterns and mechanical LBP, and not the effects of high levels of pain and disabilities of muscular activity.…”
Section: Discussionsupporting
confidence: 87%
“…Seven complained of pain in the direction of extension, three in the direction of flexion, seven in both directions, and two did not show any specific patterns. Clinically, these individuals had a score of 28.58 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Figure 2 shows the muscular latencies of all investigated muscles for the asymptomatic (2a) and LBP (2b) individuals. For the asymptomatic group, the muscular activation patterns were initiated by the semitendinosus, followed by the ipsilateral erector spinae, contralateral erector spinae and finished by the gluteus maximus.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…The results of Study III (Dankaerts et al, 2006a) demonstrated that no differences in trunk muscle activity were observed between healthy controls and a pooled nonspecific chronic LBP group in usual sitting. However, when the CS was applied differences were identified.…”
Section: Can Clinicians Agree On the Classification Of Nonspecific Chmentioning
confidence: 82%
“…Treatment for these individuals focuses on reducing fear avoidance and optimising spinal control during functional activity to avoid end-range repetitive strain, reduce spinal loading, and subsequently reduce peripheral nociceptor sensitivity [5]. Previous work has established distinct physical characteristics between two proposed MCI subgroups (Active Extension Pattern and Flexion Pattern) and healthy individuals in adolescent and adult populations, with alterations in spinal position sense, spinal kinematics and trunk muscle activity observed during static postures [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%